(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Today, the reputation and position of each country on the world stage is measured by its military-economic potential, as well as the level of awareness of information and communication systems of the population. Therefore, it is an urgent issue to systematically impart knowledge about modern technologies and information communications in all fields, including in the field of military education up to the draft. In this article, the author dwells in detail on the reforms and analyzes of the development of professional competences of students of pre-draft military education on the basis of information and communication technologies.